Formulation, Quality Characteristics, and Research Trends of Fish Balls: A Bibliometric Study - Cucu Lara Tampubolon; Adhi Kusumastuti; Octavianti Paramita (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
Fish balls are a processed fishery product that is gaining increasing attention due to their nutritional value, affordability, and acceptance across various consumer segments. This article presents a synthesis of recent research findings on the formulation, physicochemical properties, texture, sensory testing, and nutritional content of fish balls. The study results indicate that the addition of fish protein isolate (CPI/FPI), transglutaminase enzymes, and natural fillers such as tapioca, konjac, and porang can increase water holding capacity, cooking yield, and product elasticity. However, there are trade-offs in color and aroma changes that can affect consumer acceptance. Nutritionally, fish balls have been shown to have a higher protein content and a better amino acid profile than meatballs made from red meat, and have the potential to be a source of omega-3 fatty acids and functional minerals. Bibliometric analysis shows a growing research trend since 2018, although gaps remain in method standardization, the relationship between microstructure and sensory perception, and evaluation at the MSME scale. Thus, further research needs to be directed at an integrated approach that connects instrument analysis, sensory testing, and quality predictive models to support innovation, standardization, and application of research results on an industrial and MSME scale.